2011
DOI: 10.1002/ana.22521
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis normal‐appearing white matter: Pathology–imaging correlations

Abstract: Objective To determine the pathologic basis of subtle abnormalities in magnetization transfer ratio (MTR) and diffusion tensor imaging (DTI) parameters observed in normal-appearing white matter (NAWM) in multiple sclerosis (MS) brains. Methods Brain tissues were obtained through a rapid post-mortem protocol that included in situ MRI. Four types of MRI-defined regions of interest (ROIs) were analyzed: (1) Regions that were abnormal on all images (“T2T1MTR lesions”); (2) NAWM regions with slightly-abnormal MTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
203
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(227 citation statements)
references
References 45 publications
16
203
1
1
Order By: Relevance
“…The [ 11 C]TMSX-V T in the total NAWM ROI had a significant positive 32 Detailed pathology imaging correlation studies of SPMS brain have, however, demonstrated increased microglial activation and axonal degeneration associated with reduced FA in the NAWM. 3 Our study demonstrates, using a specific A2AR-binding radioligand and in vivo PET imaging, that A2ARs are increased in the NAWM of SPMS patients compared with healthy controls. The increased A2AR binding observed in the present study was associated with (1) decreased FA in DWI, (2) high EDSS, and (3) increased brain tissue loss.…”
Section: Mri Variablesmentioning
confidence: 54%
“…The [ 11 C]TMSX-V T in the total NAWM ROI had a significant positive 32 Detailed pathology imaging correlation studies of SPMS brain have, however, demonstrated increased microglial activation and axonal degeneration associated with reduced FA in the NAWM. 3 Our study demonstrates, using a specific A2AR-binding radioligand and in vivo PET imaging, that A2ARs are increased in the NAWM of SPMS patients compared with healthy controls. The increased A2AR binding observed in the present study was associated with (1) decreased FA in DWI, (2) high EDSS, and (3) increased brain tissue loss.…”
Section: Mri Variablesmentioning
confidence: 54%
“…Regarding the MRI‐histopathology correlations, it should be noted that each specimens offers the possibility of investigating several different types of cytoarchitecture, which were probed by drawing ROIs in all types of tissue. Practically, this led to the construction of a data set of 48 data points, whose size suffices to fit the regression models and evaluate correlations (other high‐impact studies on MRI‐histopathology correlation relied on the same amount of data20 or even less17). …”
Section: Discussionmentioning
confidence: 99%
“…We tested this hypothesis by evaluating the statistical associations between ROI‐wise median values of NODDI and histological indices, for a total of N = 48 ROIs (28 for the multiple sclerosis cases; 20 for the controls), similar in number to other studies 17, 20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increase in astrocytes and activated microglia appears to outweigh the decrease in oligodendrocytes in plaques, 107 which may offset prolonged relaxation times due to increased free water. In fact, a number of investigations reported a significantly reduced MTR in otherwise normal-appearing WM and GM, 92,106,[108][109][110][111][112][113][114] a close correlation between the MTR and clinical disability, 114 -117 and a potential prognostic value of magnetization transfer MR imaging. 114,118 -120 More recent studies suggest that iron-laden/activated microglia 71,121 and/or aggregates typical of small bleeding 71 cause focally increased T 2 relaxation rates and/or reduced MTR 92 within normal-appearing WM.…”
Section: Inflammationmentioning
confidence: 99%